The growth of flower bud, life history, and population structure of Rafflesia arnoldii (Rafflesiaceae) in Bengkulu, Sumatra, Indonesia - AGUS SUSATYA (Society for Indonesian Biodiversity, 2020)
Abstract. Susatya A. 2020. The growth of flower bud, life history, and population structure of Rafflesia arnoldii (Rafflesiaceae) in Bengkulu, Sumatra, Indonesia. Biodiversitas 21: 792-798. The life history of Rafflesia arnoldii R.Br. is the reflection of the complex interaction between flower bud development and the external environments in order to reach its optimal survivorship. The objectives of the study were to determine the growth of flower buds at various development stages, to reconstruct the life history, and to know the population structure of R. arnoldii. The study was carried out at Taba Penanjung, Bengkulu Province, Indonesia. Two populations consisting of 17 individual buds of R. arnoldii were selected for the research. All buds were categorized into six visible stages, mapped, measured their diameters, and recorded their fates every two weeks for six months. The exponential model of growth development was applied to reconstruct the life history. The results showed that buds from the perigone stage respectively grew 3.5 and 12 times faster than those from the bract and cupule stages. The exponential growth of flower bud was confirmed, and explained by Y = 0.785 e0.0052 X, where Y and X were respectively diameter and age of flower bud. The complete life history of R. arnoldii required 3.5 to 5 years, where a female flower needed a longer time than a male flower. The population structure of R. arnoldii was not constant, but changed dynamically over time. The dynamics of population structure was mainly caused by the high mortality of small buds and the low flower bud recruitment.